Aryl‐Heteroaryl Derivatives as Novel Wake‐Promoting Agents. (26th December 2012) - Lesur, Brigitte; Lin, Yin G.; Marcy, Val R.; Aimone, Lisa D.; Gruner, John; Bacon, Edward R.; Chatterjee, Sankar
<x xml:space="preserve">Abstract</x> In search of a next generation molecule to the novel wake‐promoting agent modafinil, a series of aryl‐heteroayl‐derived wakefulness enhancing agents (in rats) was developed. From this work, compound 16 was separated into its enantiomers to profile them individually.